RETRACTED: Eupalinolide J Suppresses the Growth of Triple-Negative Breast Cancer Cells via Targeting STAT3 Signaling Pathway - Lou, Chenghua; Chen, Yan; Zhang, Jie; Yang, Bo; Zhao, Huajun (Frontiers in Pharmacology, 2019)
Persistent activation of STAT3 plays an important role in the development of triple-negative breast cancer (TNBC) and suppression of STAT3 is considered as a novel approach for cancer therapy. In this project, we aimed to examine the anticancer activity and molecular mechanism of Eupalinolide J (EJ) in TNBC cells. The presented results demonstrated that the growth of human TNBC cells (MDA-MB-231 and MDA-MB-468 cells) was obviously inhibited by EJ. The IC50 values were 3.74 ± 0.58 and 4.30 ± 0.39 μM, respectively. Further study demonstrated that EJ suppressed the proliferation of TNBC cells mainly through cell apoptosis induction, mitochondrial membrane potential (MMP) disruption and cell cycle arrest. Meanwhile, the STAT3 and p-STAT3 in EJ-treated TNBC cells was remarkably suppressed. Importantly, silencing of STAT3 by STAT3-shRNA significantly blunted the anticancer activities of EJ in TNBC cells, suggesting that EJ suppressed cancer cell proliferation via targeting STAT3 pathway. Notably, further study demonstrated that EJ significantly promoted the degradation of STAT3 in TNBC cells. Finally, EJ exhibited an effective antitumor activity against MDA-MB-231 cells in vivo. In conclusion, we identified EJ suppressed the growth of TNBC cells via targeting STAT3 signaling pathway. These results strongly support that EJ is a promising therapeutic agent for TNBC.